Barcoding and interspecific relationships of Macaronesian Weevils (Coleoptera: Curculionoidea) - Stüben, Peter E.; Schütte, André; Astrin, Jonas J. (Contributions to Entomology = Beiträge zur Entomologie, 2021)
In an integrative taxonomic approach, this study presents mitochondrial CO1 barcodes for 468 of the 735 so far described Lauri-Macaronesian weevil (Curculionoidea) species and subspecies in 1388 samples. A Bayesian tree (electronic supplement) provides insights into within-species relationships, without aiming at phylogenetic accuracy above genus level. With the exception of a few discussed cases, the present dataset of DNA barcodes allows a reliable re-identification and remarkable differentiation of species and will accelerate the discovery of new weevil species from the Canary, Madeira and Azores archipelagos. Only in a single case, the similar species Rhinoncus castor and R. bruchoides (Ceutorhynchinae) from Madeira, did the molecular (re)identification reveal an unresolvable contradiction with our morphological species identification. In many cases, morphological determinations were bolstered by comparisons with the type material. Sequenced specimens were mounted and deposited in a reference collection for later re-determinations.
Keywords: Integrative taxonomy; CO1; morphology; Bayesian tree; cryptic species; young species splits; species complexes; Canary Islands; Madeira archipelago; Savage Islands; Azores